The End of the Beginning? Mining, sacred geographies, memory and performance in Lihir - Bainton, Nicholas A. (The Australian journal of anthropology, 2012)
This article explores the critical ways in which the relationship between landscape and memory is mediated by performance—through song, dance, ritual and the movements of the living and the dead. In the Lihir group of islands, in Papua New Guinea, these acts of memorialisation are rehearsed on a remarkable stage, an involuted cosmography or sacred geography in which the cosmological point of origin, the sacred rock of Ailaya, is also the ultimate destination for all human and spirit forms. Spirit beings are held to have emerged from the Ailaya, spreading across the island group, their tracks charting the links amongst distant clan members and the networks of alliance between trading partners. It is to the Ailaya that the spirits of deceased Lihirians must return, following preparatory mortuary rites and sung along a route that recalls the spirit connections. This teleological process is mapped through an account of the performance of relationships between people and land, to which an additional layer of complexity is added by the presence of a giant gold mine, in which the Ailaya is again the central feature.